3D printing technologies: FDM and Polyjet evaluations in the manufacture of automobile auto parts - Briceño-Martínez, Bryan Jhon; Llanes Cedeño, Edilberto Antonio; Rocha-Hoyos, Juan Carlos; Chamba, Edwin; Cuasapud, Diego; Cárdenaz-Yánez, Andrés (Enfoque UTE, 2019)
The objective of the study was to evaluate the 3D printing technologies made by Molded Deposition Modeling (FDM) and PolyJet from mechanical tests with Acrylonitrile Styrene Acrylate (ASA) and VeroWhitePlus RGD 835 materials, for the selection of the material and adequate technology in the manufacture of air ducts applied to automotive auto parts. To achieve the objective, mechanical tensile tests were carried out on specimens manufactured by both technologies, according to ASTM D638-14 for tensile tests and for bending tests according to ASTM 790; To evaluate the behavior of air flow in the pipeline, the air duct used in the Toyota Stout 2200 pick-up truck modeled by the Ansys Student software was selected as the case study. The results showed that the VeroWhitePlus RDG 835 material used in the construction of the duct by means of the PolyJet technology presented the best results with a yield strength of 4.7 MPa and a maximum bending stress of 28 MPa.